Natural Semantic Metalanguage Analysis of English Speech Act Verb ‘Inform’ - Ardiantari, Desak Putu Salshabila (Universitas Pendidikan Ganesha, 2023)
Generally, every language has a lexicon that is grouped into classified verbs. Each verb can be broken down into some specific subtypes. Particularly in English, verbs are semantically divided into several subtypes. Verbs such as tell, ask, inform, offer, forgive, and others are belonging to the types of verbs of speech or speech acts. This study aims to analyze natural semantic metalanguage analysis of English speech act verb of inform. In collecting data is using observational method. Therefore, the theory of natural semantic metalanguage (NSM) is used to analyze the data taken from the American Corpus (COCA). By way of explication, the particular lexicon is explained thoroughly to reveal the subtle meaning of semantic features without any bias. The research argues that the four subtypes of the speech act verb